Social Innovation as an instrument for Public Innovation (Revista Galega de Economía)
This article explores the relationship between the concepts of Social Innovation and Public Innovation. The article shows and expands on the links between Public Innovation and Social Innovation, also analysing the way in which such links are produced, especially through the Governance processes and the Public Administration Innovation. Finally, the paper emphasises the idea that all public innovation represents a particular form of social innovation and vice versa. Social innovation can contribute to improving the ways in which public innovation is undertaken.